Selling Hospice. Issue 4 (December 2014) - Halabi, Sam
<x xml:space="preserve">Abstract</x> Americans are increasingly turning to hospice services to provide them with medical care, pain management, and emotional support at the end of life. The increase in the rates of hospice utilization is explained by a number of factors including a "hospice movement" dating to the 1970s which emphasized hospice as a tool to promote dignity for the terminally ill; coverage of hospice services by Medicare beginning in 1983; and, the market for hospice services provision, sustained almost entirely by governmental reimbursement. On the one hand, the growing acceptance of hospice may be seen as a sign of trends giving substance to the death‐with‐dignity movement and the growing strength of end‐of‐life decision‐makers and planners who integrate medical, community, family and spiritual networks. On the other hand, the precise relationship between the death‐with‐dignity and commercial processes driving hospice utilization rates are not well understood. On May 2, 2013, the U.S. Government intervened in a lawsuit brought by former hospice employees alleging that behind Vitas Innovative Hospice Care, the largest for‐profit hospice service provider in the United States, lie an intricate web of incentives for patient intake nurses, physicians and marketers which not only drove hospice patients to use more expensive (and medically unnecessary) crisis care services, but influenced patient and family decisions as to whether or not to discontinue curative treatment. The corporate, investment, and regulatory history behind Vitas provides an important insight into the market realities behind Americans' embrace of hospice care and the risks to patient autonomy and health that accompany the commercialization of this ethically and morally complex health care service.